Marriage Counseling: A Pre & Past marriage Notion - Deo, Sapna Sukrut; Deo, Sukrut Makarand (International Journal of Psychosocial Rehabilitation, 2020)
With the development of industrialization and urbanization, institution of marriage has also changed. People are busier which is also giving rise to many new conflicts in a marriage tie. To tackle these problems a new concept came into existence known as marriage counseling. Marriage counseling aims at providing couples counseling needed to make their marriage tie strong and improve relations. It is done by an unbiased counselor. He focuses on resolving conflict, identify strong points of relationship between two persons and try to mitigate their differences. Skills such as healthy communication, respect for partner and solving out differences are among many skills a couple acquired while going through marriage counseling. Marriage counseling may require more than one counseling session. Concept of pre marriage counseling is also developed. Pre marriage counseling tracks whether person who are going to marry are on same track or not. This article discusses in detail meaning of marriage, counseling and marriage counseling. It further discusses qualities which must be there in a counselor, how counseling can help and concept of pre marriage counseling.